2008
DOI: 10.1007/978-0-387-73693-8_21
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Bursting in Small Networks of Model Conditional Pacemakers in the pre-Bötzinger Complex

Abstract: Abstract. This paper summarizes some lessons learned from the computational study of bursting oscillations in small networks of model pre-Bötzinger complex (pBC) neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…This raises an important question: what is the significance of intrinsic bursting properties for the generation of the breathing rhythm? Theoretical studies have shown that the presence of intrinsic bursters is not required to generate network-wide bursting (Rubin 2006, 2008), but that intrinsic bursters can create a more robust network with a wider range of output frequencies (Purvis et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…This raises an important question: what is the significance of intrinsic bursting properties for the generation of the breathing rhythm? Theoretical studies have shown that the presence of intrinsic bursters is not required to generate network-wide bursting (Rubin 2006, 2008), but that intrinsic bursters can create a more robust network with a wider range of output frequencies (Purvis et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Mathematical models can be particularly helpful for generating experimentally testable hypotheses. A variety of models have been developed for the respiratory CPG [18,19,20,21,22,23,24,25], for chemosensory feedback-based regulation schemes [26,27,28], and for cardiopulmonary gas exchange [29]. See [30,31] for a review.…”
Section: Quantitative Modeling Approachmentioning
confidence: 99%